Opportunities and Challenges for Local Governments in Increasing Local Revenues through Fisheries Trade System Reform Marine Capture in Bintan Regency - Lamidi Lamidi; Dicky Novalino; Ilham Yuri Nanda (Journal of Maritime Policy Science, 2025)
This study aims to analyze the role of local government in utilizing marine capture fisheries potential to increase regional revenue in Bintan Regency, Riau Islands Province. Employing a descriptive qualitative approach, the study illustrates the current conditions of marine and fisheries sector governance, while identifying institutional challenges and opportunities for trade system reform. The findings reveal that although capture fisheries production has steadily increased, its contribution to regional revenue remains significantly low. This is primarily due to suboptimal local governance, the absence of Fish Auction Centers (TPI), and the dominance of a closed distribution system controlled by middlemen (tauke), which weakens fishers’ bargaining power and eliminates potential local revenue from levies. The local government faces multiple structural challenges, including weak regulatory frameworks, lack of integrated production data, and the institutional disempowerment of fisher communities. Nevertheless, there are strategic opportunities that can be leveraged through the professional development and management of TPI. These centers can serve as critical instruments for ensuring price transparency, strengthening production records, increasing local revenue through levies, empowering fishers' cooperatives, and breaking the dependency on the tauke system. The study recommends the need for integrated, institution-based, and context-specific policies to support a sustainable and inclusive reform of the capture fisheries trade system in Bintan Regency.